The impact of corporate governance on firms' value in an emerging country: The mediating role of corporate social responsibility and organisational identification - Thanh Tiep Le; Van Kha Nguyen (Cogent Business & Management, 2022)
Corporate governance is a field that is attracting great attention in the world due to its importance to the destiny of enterprises. More importantly, in the context of escalating environmental and social problems, how businesses are governed towards a balance of economic, social and environmental values receives significant concern by the stakeholders of the business in the globe. This study aims to understand intensively the impact of corporate governance on firm value by exploring the mediation mechanism of corporate social responsibility and organisational identification in the relationship between corporate governance and firm value. This study uses the covariance-based structural equation modelling (CB-SEM) analysis technique because of its suitability for organisational and management research such as the present study. This study focuses on the small and medium-sized enterprises (SMEs) in emerging economies due to its importance as outlined in the introduction below. The contribution of this study is the provision of the additional empirical evidence on the important role of corporate governance in increasing firm value. In addition, the empirical evidence on the mediating influence of corporate social responsibility and organisational identification in the relationship between corporate governance and firm value deserves the main interest of this study. Furthermore, its application to the SME context in emerging economies reinforces the novelty of this study. Based on the findings of this study, theoretical and managerial implications are also proposed. The findings of this study may be of interest to entrepreneurs, top management, academics and researchers.
Keywords: 650; Corporate governance; corporate social responsibility; emerging country; firm's value; organisational identification; SMEs